Kepuasan kerja dan faktor-faktor lain yang mempengaruhi proses berkesatuan-sekerja : suatu peninjauan di kawasan perindustrian Pending - Ho, Khee Fatt (University Malaysia Sarawak, UNIMAS., 1997)
Establishment of harmonious industrial environment is a major factor that contributes to the development of manufacturing sector in Malaysia. It is believed that creation of good employer-employees relationship through unionisation process might help to establish a harmonious workplace.